2006
DOI: 10.1111/j.1745-7254.2006.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Chiral selective effects of doxazosin enantiomers on blood pressure and urinary bladder pressure in anesthetized rats

Abstract: Aim: To study chiral selective effects of doxazosin enantiomers on blood pressure and urinary bladder pressure in anesthetized rats. Methods: In anesthetized rats, the carotid blood pressure, left ventricular pressure of the heart and the urinary bladder pressure were recorded. Results: Administration of S-doxazosin at 0.25, 2.5, 25, and 250 nmol/kg iv produced a dose-dependent decrease in blood pressure, but its depressor effect was significantly weaker than that induced by R-doxazosin and racemic-doxazosin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…(Ϯ)DOX and its enantiomers have all proved to be potent antagonists with balanced activity across the cloned human ␣ 1A -, ␣ 1B -, and ␣ 1D -adrenoceptor subtypes expressed in rat-1 fibroblast cell lines (Hatano et al 1996). Recently, we unexpectedly found that (-)DOX decreased the carotid blood pressure more weakly than (ϩ)DOX and (Ϯ)DOX in anesthetized rats, but its effect on the vesical micturition pressure was similar to (ϩ)DOX and (Ϯ)DOX in anesthetized rats and guinea pigs (Ma et al 2006;Tian and Ren 2007), showing chiral recognition of (ϩ)DOX and (-)DOX in an intact biological system. In a preliminary experiment, we further found a negative inotropic effect evoked by (Ϯ)DOX at concentrations much higher than those needed to block ␣ 1 -adrenoceptors.…”
Section: Introductionmentioning
confidence: 72%
“…(Ϯ)DOX and its enantiomers have all proved to be potent antagonists with balanced activity across the cloned human ␣ 1A -, ␣ 1B -, and ␣ 1D -adrenoceptor subtypes expressed in rat-1 fibroblast cell lines (Hatano et al 1996). Recently, we unexpectedly found that (-)DOX decreased the carotid blood pressure more weakly than (ϩ)DOX and (Ϯ)DOX in anesthetized rats, but its effect on the vesical micturition pressure was similar to (ϩ)DOX and (Ϯ)DOX in anesthetized rats and guinea pigs (Ma et al 2006;Tian and Ren 2007), showing chiral recognition of (ϩ)DOX and (-)DOX in an intact biological system. In a preliminary experiment, we further found a negative inotropic effect evoked by (Ϯ)DOX at concentrations much higher than those needed to block ␣ 1 -adrenoceptors.…”
Section: Introductionmentioning
confidence: 72%
“…(-)-(R)-doxazosin was shown to decrease the carotid blood pressure more weakly than (+)-(S)doxazosin in anesthetized rats. 8 The chiral carbon atom in the molecular structure of doxazosin does not affect the therapeutic activity at α 1A -adrenoceptors in the rabbit prostate, but it significantly affects the blocking activity at α 1Dadrenoceptors in the rat aorta. [9][10][11] Moreover, in rat and rabbit heart tissues, (+)-(S)-doxazosin significantly decreases the atrial rate and produces negative inotropic effects; however, (-)-(R)-doxazosin produces positive inotropic effects in the atria via an α 1 -adrenoceptor-independent mechanism.…”
Section: Abstract: Pharmacokinetics;mentioning
confidence: 99%
“…Doxazosin is a safe and efficacious treatment option for lower urinary tract symptoms (LUTS) in patients with benign prostatic hyperplasia (BPH), [1][2][3] and as an add-on drug in combination therapy to achieve target blood pressures. 8 The chiral carbon atom in the molecular structure of doxazosin does not affect the therapeutic activity at α 1A -adrenoceptors in the rabbit prostate, but it significantly affects the blocking activity at α 1Dadrenoceptors in the rat aorta. The (+)-(S)-doxazosin and (-)-(R)-doxazosin do not have the same biological activity.…”
mentioning
confidence: 99%
“…Previously, we reported that hypotensive responses to intravenously administered (-)doxazosin were significantly smaller than those to (+)doxazosin and (±)doxazosin and that (+)doxazosin treatment produced a larger decrease in the BP than (±)doxazosin treatment in acute experiments on anesthetized rats [9] . In the present study, long-term (12-week) administration of racemic doxazosin and its enantiomers to the conscious rat revealed unexpected results.…”
Section: Discussionmentioning
confidence: 99%
“…(±)Doxazosin and its enantiomers all are proved to be potent antagonists with balanced activity across the cloned human α 1A -, α 1B -, and α 1D -adrenoceptor subtypes expressed in rat-1 fibroblast cell lines [8] . However, we recently found that (-)doxazosin treatment decreased the carotid blood pressure to an extend less than those induced by (+)doxazosin and (±)doxazosin treatment in anesthetized rats, but its effect on the vesical micturition pressure was similar to (+)doxazosin and (±)doxazosin treatment in anesthetized rats and guinea pigs [9,10] . These results indicated the chiral recognition of (+)doxazosin and (-)doxazosin in an intact biological system.…”
Section: Introductionmentioning
confidence: 99%